Challenges in calculating the bandgap of triazine-based carbon nitride structures. Issue 10 (22nd February 2017) - Steinmann, Stephan N.; Melissen, Sigismund T. A. G.; Le Bahers, Tangui; Sautet, Philippe
Abstract : Graphitic carbon nitrides form a popular family of materials, particularly as photoharvesters in photocatalytic water splitting cells. Abstract : Graphitic carbon nitrides form a popular family of materials, particularly as photoharvesters in photocatalytic water splitting cells. Recently, relatively ordered g-C3 N4 and g-C6 N9 H3 were characterized by X-ray diffraction and their ability to photogenerate excitons was subsequently estimated using density functional theory. In this study, the ability of triazine-based g-C3 N4 and g-C6 N9 H3 to photogenerate excitons was studied using self-consistent GW computations followed by solving the Bethe–Salpeter Equation (BSE). In particular, monolayers, bilayers and 3D-periodic systems were characterized. The predicted optical band gaps are in the order of 1 eV higher than the experimentally measured ones, which is explained by a combination of shortcomings in the adopted model, small defects in the experimentally obtained structures and the particular nature of the experimental determination of the band gap.